Rats remember items in context using episodic memory - Panoz-Brown, Danielle (Curr Biol, 2016)
Vivid episodic memories in people have been characterized as the replay of unique events in sequential order [1–3]. Animal models of episodic memory have successfully documented episodic memory of a single event (e.g., [4–8]). However, a fundamental feature of episodic memory in people is that it involves multiple events, and notably, episodic-memory impairments in human diseases are not limited to a single event. Critically, it is not known whether animals remember many unique events using episodic memory. Here we show that rats remember many unique events and the contexts in which the events occurred using episodic memory. We used an olfactory memory assessment in which new (but not old) odors were rewarded using 32 items. Rats were presented with 16 odors in one context and the same odors in a second context. To attain high accuracy, the rats needed to remember item in context because each odor was rewarded as a new item in each context. The demands on item-in-context memory were varied by assessing memory with 2, 3, 5, or 15 unpredictable transitions between contexts, and item-in-context memory survived a 45-min retention-interval challenge. When the memory of item in context was put in conflict with non-episodic familiarity cues, rats relied on item in context using episodic memory. Our findings suggest that rats remember multiple unique events and the contexts in which these events occurred using episodic memory and support the view that rats may be used to model fundamental aspects of human cognition.